Exploration on the relationship between hypoxia inducible factor-1α and morbidly adherent placenta - J.Y. Yan; P.P. Chen; L.L. Jiang; H.L. Zhang; Q. Han; R.X. Chen; Q.J. Zhang (IMR Press, 2020)
Objective: This study aims to explore the role of hypoxia inducible factor-1α (HIF-1α) in morbidly adherent placenta (MAP). Materials and Methods: Ten pregnant women with placenta increta, 20 pregnant women with placenta previa, and 30 normal pregnant women as controls participated in the present study. Real-time reverse transcription polymerase chain reaction (RT-PCR) was used to measure the mRNA expression of HIF-1α in the placenta. Enzyme-linked immunosorbent assay (ELISA) was performed to analyze the HIF-1α protein levels in the placenta. Results: The mean expression of placental HIF-1α in the placenta increta and placenta previa groups was significantly higher than that in the normal placenta. The level of placental HIF-1α in the placenta increta was significantly higher than that in the placenta previa (p < 0.05). The level of placental HIF-1α had no obvious correlation with the accreta site and umbilical cord insertion. Conclusion: The morbidly of adherent placenta is closely correlated to adverse pregnancy outcomes during the perinatal period. Placental HIF-1α is associated with morbidly adherent placenta.